Stable Clinical Outcomes When a Stroke Thrombectomy Program Is Started in an Experienced Cardiology Cath Lab - Sulženko, Jakub; Kožnar, Boris; Peisker, Tomáš; Vaško, Peter; Vavrová, Jana; Štětkářová, Ivana; Widimský, Petr (JACC. Cardiovascular interventions, 2021)
OBJECTIVES: This study analyzed the learning curve effect when a new stroke thrombectomy program was initiated in a cardiac cath lab in close cooperation with neurologists and radiologists. BACKGROUND: Mechanical thrombectomy has proven to be the best treatment option for ischemic stroke patients, but this method is not widely available. METHODS: An endovascular treatment program for acute ischemic strokes was established in the cardiac cath lab of a tertiary university hospital in 2012. The decision to perform catheter-based thrombectomy was made by a neurologist and was based on acute stroke clinical symptoms and computed tomography angiographic findings. Patients with a large vessel occlusion of either anterior or posterior circulation were enrolled. The primary endpoint was the functional neurological outcome (Modified Rankin Scale [mRS] score) of the patient at 3 months. A total of 333 patients were enrolled between October 2012 and December 2019. RESULTS: The clinical (mRS) outcomes did not vary significantly across years 2012 to 2019 (mRS 0 to 2 was achieved in 47.9% of patients). Symptomatic intracerebral hemorrhage occurred in 19 patients (5.7%). Embolization in a new vascular territory occurred in 6 patients (1.8%). CONCLUSIONS: When a catheter-based thrombectomy program was initiated in an experienced cardiac cath lab in close cooperation between cardiologists, neurologists, and radiologists, outcomes were comparable to those of neuroradiology centers. The desired clinical results were achieved from the onset of the program, without any signs of a learning curve effect. These findings support the potential role of interventional cardiac cath labs in the treatment of acute stroke in regions where this therapy is not readily available due to the lack of neurointerventionalists.
Keywords: výsledek terapie; Cardiologists; kardiologové; neurocardiology; kardiologie; acute ischemic stroke; Thrombectomy; learning curve; Humans; Stroke; Cardiology; endovascular treatment; Treatment Outcome; cévní mozková příhoda; lidé; catheter-based thrombectomy; trombektomie